2022
DOI: 10.1021/acs.langmuir.2c01199
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Loaded Nanocarriers Composed of Cholesteryl Oleate Crystal Cores and Multiple-Nanosheet Shells of γ-Cyclodextrin Inclusion Complex Crystals

Abstract: In this study, we prepared drug-loaded nanocarriers made of cholesteryl oleate (ChO) and γ-cyclodextrin (γ-CD). A nanosuspension (nanosuspension-I, NS-I) containing nanoparticles with a mean size of approximately 170 nm was obtained through the solvent-diffusion method using ethanol. A second nanosuspension (nanosuspension-II, NS-II), which was prepared by freeze-drying and redispersion of NS-I, exhibited an increased particle size of approximately 210 nm. Cryogenic transmission electron microscopy (cryo-TEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…To further evaluate the drug loading capacity of our polymer nanodiscs, doxorubicin (DOX) was encapsulated with a drug loading content of 9.5 wt % and a loading efficiency of 19.6 % (Figure S21). The results were comparable to the poly(ethyl glyoxylate)‐ b ‐poly(ethylene oxide) nanoparticles reported by the Gillies group earlier [51] and exhibited higher loading capacity than common 2D polymer materials with crystalline cores [52] …”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…To further evaluate the drug loading capacity of our polymer nanodiscs, doxorubicin (DOX) was encapsulated with a drug loading content of 9.5 wt % and a loading efficiency of 19.6 % (Figure S21). The results were comparable to the poly(ethyl glyoxylate)‐ b ‐poly(ethylene oxide) nanoparticles reported by the Gillies group earlier [51] and exhibited higher loading capacity than common 2D polymer materials with crystalline cores [52] …”
Section: Methodssupporting
confidence: 86%
“…The results were comparable to the poly(ethyl glyoxylate)-b-poly(ethylene oxide) nanoparticles reported by the Gillies group earlier [51] and exhibited higher loading capacity than common 2D polymer materials with crystalline cores. [52] In conclusion, we have successfully synthesised a tadpole-like amphiphilic BBC with a rod-coil architecture. While a coil-rod-coil bottlebrush-containing macromolecule has been studied before, [27,29] polymer discs were only obtained in organic solvent mixtures and featured no stimuli-responsive properties.…”
mentioning
confidence: 86%
“…ChO (0.05 mmol)/γ‐CD (1.5 mmol) nanoparticles were prepared by the solvent diffusion method in which ethanol containing ChO was added to a γ‐CD aqueous solution. 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it can be speculated that these regular lamellar crystals (large particles) were amphiphilic lamellar inclusions formed by further self-assembly of the supramolecular (small particles) formed by β-CD and GO. Similarly, Ishimoto et al ( 35 ) also confirmed the formation of crystalline flake shells between host and guest in the study of the formation of γ-CD and cholesterol oleate in drug-carrying nanocarriers.…”
Section: Resultsmentioning
confidence: 68%